2012
DOI: 10.1021/cs300090h
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Nanocatalysts Immobilized on Functionalized Resin for the Direct Synthesis of Hydrogen Peroxide from Hydrogen and Oxygen

Abstract: The direct synthesis of hydrogen peroxide (DSHP) from H2 and O2 is conceptually the most ideal and straightforward reaction for producing H2O2 in industry. However, precisely tailored catalysts are still in progress for large scale production. Here, we report highly efficient and industrially relevant catalysts for the direct synthesis of H2O2 from H2 and O2 prepared by the immobilization of Pd nanocatalysts onto a functionalized resin. The continuous production of 8.9 wt % H2O2 and high productivity (180 g of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 31 publications
(39 reference statements)
0
34
0
Order By: Relevance
“…Choudhary and Samanta reported significant Pd chemical leaching from the catalyst when using phosphoric acid as promoter in concentration over 0.3 M. Chemically induced leaching was spectroscopically confirmed by observing a loss of uniform morphology of Pd nanoparticles [147]. On the other hand, physical detachment of nanoparticles from silica with no evidence of chemical leaching was confirmed by Kim et al through TEM and XRD analyses when using phosphoric acid in concentration below 0.3 M [115,169]. In order to improve retention of the Pd nanoparticle, the core@shell structure is being actively studied [172][173][174].…”
Section: Influence Of Surface Morphologymentioning
confidence: 82%
See 2 more Smart Citations
“…Choudhary and Samanta reported significant Pd chemical leaching from the catalyst when using phosphoric acid as promoter in concentration over 0.3 M. Chemically induced leaching was spectroscopically confirmed by observing a loss of uniform morphology of Pd nanoparticles [147]. On the other hand, physical detachment of nanoparticles from silica with no evidence of chemical leaching was confirmed by Kim et al through TEM and XRD analyses when using phosphoric acid in concentration below 0.3 M [115,169]. In order to improve retention of the Pd nanoparticle, the core@shell structure is being actively studied [172][173][174].…”
Section: Influence Of Surface Morphologymentioning
confidence: 82%
“…Park and Fierro et al [99,[111][112][113][114][115] studied the performance of Pd catalysts supported on silica functionalized with sulfonic groups and found that the SO 3 H functional groups not only can promote the generation of H 2 O 2 but also make it possible for the process to be operated using less inorganic acid, thus reducing reactor corrosion and the loss of active metal. The role of sulfonic groups was tested also in the case of sulfonated cation exchange polystyrene resins.…”
Section: Effect Of the Aciditymentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with the literature, only Biasi et al found similarly low productivities of 180 mol H2O2 /kg Pd /h using methanol without additives as solvent in a trickle bed reactor. In continuous flow experiments, most of the groups found productivities between 1500 and 6000 mol H2O2 /kg Pd /h [41,43,44,48,52,54,55,62]; only Kanungo et al [46] stood out with achieving a productivity of 1,4300 mol H2O2 /kg Pd /h by using coated microchannel capillaries. The reactors used in the literature were mostly trickle bed reactors, stirred autoclaves or microchannel trickle beds, and hence tri-phasic systems with the related safety issues.…”
Section: System Productivitymentioning
confidence: 99%
“…[3,4] To provide an alternative, extensive efforts have been devoted to achieving the direct synthesis of H 2 O 2 from hydrogen (H 2 ) and oxygen (O 2 ) by using heterogeneous precious-metal catalysts (mainly Pd, Au, or Au-Pd). [3][4][5][6][7][8][9][10][11][12] This direct process suffers from serious problems such as unfavorable high-pressure conditions and relatively low yields owing to undesired side reactions such as formation of [3][4][5][6][7][8][9][10][11][12] For this reason, selectivity in the direct synthesis of H 2 O 2 from H 2 and O 2 has been limited. In addition, it has been quite difficult to elucidate the heterogeneous catalytic mechanism as compared with the homogeneous catalytic mechanism, in which intermediates can be detected.…”
mentioning
confidence: 99%